2009
DOI: 10.3390/s91008278
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Layer Active Predictive Congestion Control Protocol for Wireless Sensor Networks

Abstract: In wireless sensor networks (WSNs), there are numerous factors that may cause network congestion problems, such as the many-to-one communication modes, mutual interference of wireless links, dynamic changes of network topology and the memory-restrained characteristics of nodes. All these factors result in a network being more vulnerable to congestion. In this paper, a cross-layer active predictive congestion control scheme (CL-APCC) for improving the performance of networks is proposed. Queuing theory is appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…For the transmission of the data, optimization approach based on power interference controlling [1], cross layer coding [2] and proposed joint cross layer coding is carried out. The packet forwarding of the three methods are then recorded.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the transmission of the data, optimization approach based on power interference controlling [1], cross layer coding [2] and proposed joint cross layer coding is carried out. The packet forwarding of the three methods are then recorded.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the computation time for interference based controlling mechanism is very low than the other two method. However in the case of memory control mechanism [2], the time taken is higher due to the computation of memory buffering and optimization of allocation. However for the proposed approach, the processing time is still higher about 1.5 units, due to the optimization of multiple factors simultaneously.…”
Section: Figure 5: Overall Processing Time For the Three Methodsmentioning
confidence: 99%
See 3 more Smart Citations